Pengaruh Pendidikan Kesehatan Dengan Video Animasi Terhadap Pengetahuan Remaja Tentang Menstruasi - PUTRI ARSY ADELIA; Yuniza Yuniza; Miskiyah Tamar (IKesT Muhammadiyah Palembang, 2024)
One of the first phase in an adolescent’s life is puberty. Adolescent puberty is defined as a transitional period from childhood to adulthood with an age limit of 10-19 years, which is marked by physical and psychological changes. In the adolescent phase, the role of parents is very important. The beginning of a woman’s puberty is the first menstruation which refers to the release of blood from the uterine wall for the first time for a woman with an age range of 10-14 years which indicates that she has entered the period of Mature religiously and is mature to start reproducing. Lack of information and knowledge about reproductive health, especially menstruation, affects adolescents’ perception of menstruation. One way to increase knowledge is to provide health education. One of the health educations provided can use animated videos. Objective: To determine the effect of Health education with animated videos on adolescent knowledge about menstruation. Research Method: This study is a quantitative study using a pre-experimental one group pretest-posttest design. The sampling technique used a total sampling of 61 respondents. Data analysis used the Paired Sample T-test. Results: This study obtained an average value before knowledge of 9.90 and after knowledge of 13.59. Based on the statistical test of knowledge, the P-value = 0.000 was obtained. Conclusion: Health education with animated videos has an effect on students’ knowledge about menstruation.